2014
DOI: 10.1089/hum.2013.182
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Transduction by Helper-Dependent Adenoviral Vectors via Intraductal Delivery

Abstract: Pancreatic gene transfer could be useful to treat several diseases, such as diabetes mellitus, cystic fibrosis, chronic pancreatitis, or pancreatic cancer. Helper-dependent adenoviral vectors (HDAds) are promising tools for gene therapy because of their large cloning capacity, high levels of transgene expression, and long-term persistence in immunocompetent animals. Nevertheless, the ability of HDAds to transduce the pancreas in vivo has not been investigated yet. Here, we have generated HDAds carrying pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…With respect to clinical applications, the substitution of first generation adenoviral vectors with other type of vectors that are less immunogenic and toxic than adenovirus, such as AAV or helper-dependent adenoviral (HD-Ad) vectors, is desirable [ 47 ]. Our laboratory has shown that efficient and persistent transduction of the pancreas in vivo is possible using AAV and HD-Ad vectors via intraductal administration [ 48 , 49 ]. Thus, to induce acinar-to-β cell reprogramming in immunocompetent animals and humans, it might be feasible to co-express PNM and miRNAs of interest in vivo (for instance, those that are activated by first generation adenoviral vectors) using AAV or HD-Ad vectors.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to clinical applications, the substitution of first generation adenoviral vectors with other type of vectors that are less immunogenic and toxic than adenovirus, such as AAV or helper-dependent adenoviral (HD-Ad) vectors, is desirable [ 47 ]. Our laboratory has shown that efficient and persistent transduction of the pancreas in vivo is possible using AAV and HD-Ad vectors via intraductal administration [ 48 , 49 ]. Thus, to induce acinar-to-β cell reprogramming in immunocompetent animals and humans, it might be feasible to co-express PNM and miRNAs of interest in vivo (for instance, those that are activated by first generation adenoviral vectors) using AAV or HD-Ad vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Their data proved that most of the vector genomes were found in the liver, lungs, and spleen via intravenous administration. In contrast, a highly significant reduction of systemic dissemination of vector genomes to these off‐target organs was detected when the same dose of vectors was administered through the intrapancreatic duct …”
Section: Introductionmentioning
confidence: 94%
“…In contrast, a highly significant reduction of systemic dissemination of vector genomes to these off-target organs was detected when the same dose of vectors was administered through the intrapancreatic duct. 12 These studies point to the fact that the intrapancreatic ductal injection route would result in a better transduction of the target organ with reduced systemic dissemination. An additional important benefit derives from the fact that intrapancreatic duct injection is an approved clinical method.…”
Section: Introductionmentioning
confidence: 99%
“…HDAd eliminate the problem of viral gene expression in transfected cells, which accompanies AAV [45]. HDAd have been reported to show long-term expression of transgenes in the pancreas [46]. …”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%